Study of Quran in Indo-Pak Subcontinent: Historical Examination and Current Perspectives (Al-Qamar, 2022)
The Quran has had an indelible impact on shaping the religious, cultural, and political landscapes of the Indo-Pak subcontinent, which hosts one of the world's most significant Muslim populations. This article embarks on a comprehensive exploration of the study of the Quran and its influence in this region, revealing its deep and multifaceted impacts.Starting from the historical context, the paper examines the traditional methods of Quranic study, including 'Tafsir,' 'Tajweed,' 'Hifz,' and 'Qira'at,' highlighting their influence on the religious educational system. It then transitions to discussing modern scholarly approaches, such as textual analysis, comparative study, contextual interpretation, and the use of technology in Quranic study.The socio-cultural dynamics and political implications of Quranic teachings in the Indo-Pak subcontinent are thoroughly analyzed. The Quran has not only shaped societal norms and influenced arts, literature, and culture, but it has also been a guiding force for political ideologies and a tool for mobilization.The article concludes by reaffirming the continued importance of the Quran in shaping the region's future trajectories, emphasizing the need for ongoing scholarly engagement with its study. This investigation illuminates the relationship between religious texts and societal contexts, contributing to a broader understanding of Islamic studies in a significant geographical region.
Keywords: Indo-Pak Subcontinent; Quran; Quranic Studies; Islamic Studies; Traditional Education; Modern Scholarly Approaches; Socio-cultural Influence; Political Dynamics